2023
DOI: 10.3390/vaccines11030611
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory Commensal Bacterium Corynebacterium pseudodiphtheriticum as a Mucosal Adjuvant for Nasal Vaccines

Abstract: Previously, we demonstrated that nasally administered Corynebacterium pseudodiphteriticum 090104 (Cp) or its bacterium-like particles (BLPs) increase the resistance of mice against bacterial and viral respiratory pathogens by modulating the innate immunity. In this work, we evaluated the ability of Cp and BLPs to stimulate alveolar macrophages, and to enhance the humoral immune response induced by a commercial vaccine against Streptococcus pneumoniae. In the first set of experiments, Cp or the BLPs were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…This observation aligns with our earlier findings, which focused on early infection assessed at day 2 post-challenge [11]. The protective effect can be credited to the bolstering of innate immunity and the heightened activation of antigen-presenting cells [11,13], resulting in a strengthening of both humoral and cellular adaptive immune responses. The impact of Cp 090104 and CP-derived BLPs on adaptive immunity was apparent in the increased levels of antibodies, TNF-α, IFN-γ, and IL-4 found in the respiratory mucosa and bloodstream of the treated mice compared with the control mice.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This observation aligns with our earlier findings, which focused on early infection assessed at day 2 post-challenge [11]. The protective effect can be credited to the bolstering of innate immunity and the heightened activation of antigen-presenting cells [11,13], resulting in a strengthening of both humoral and cellular adaptive immune responses. The impact of Cp 090104 and CP-derived BLPs on adaptive immunity was apparent in the increased levels of antibodies, TNF-α, IFN-γ, and IL-4 found in the respiratory mucosa and bloodstream of the treated mice compared with the control mice.…”
Section: Discussionsupporting
confidence: 91%
“…(b) Cp 090104 and CP-derived BLPs enhance the adaptive immune responses induced by pneumococcal vaccines and boost resistance to primary pneumococcal infection. Our previous research showed that nasal priming with Cp 090104 and CP-derived BLPs enhances the effectiveness of the pneumococcal conjugate vaccine Prevenar ® 13 (PCV) by acting as mucosal adjuvants [13]. This study aimed to further investigate the adjuvant properties of Cp 090104 or CP-derived BLPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations